2022
DOI: 10.3389/fphar.2021.823285
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Dimethyl Itaconate Against Hepatocellular Carcinoma via Activation of the e/iNOS-Mediated NF-κB–Dependent Apoptotic Pathway

Abstract: Hepatocellular carcinoma (HCC) is one of the most common tumors affecting a large population worldwide, with the fifth and seventh greatest mortality rates among men and women, respectively, and the third prime cause of mortality among cancer victims. Dimethyl itaconate (DI) has been reported to be efficacious in colorectal cancer by decreasing IL-1β release from intestinal epithelial cells. In this study, diethylnitrosamine (DEN)-induced HCC in male albino Wistar rats was treated with DI as an anticancer drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The use of DI is currently proposed as a novel putative treatment strategy for several inflammatory-mediated diseases including cardiovascular diseases where a recent report showed that DI-loaded nanofibers reduce inflammation and help to repair myocardic infarction [16,[22][23][24][25]. In the context of cancer, DI showed anticancer activity in mouse models of hepatocellular carcinoma [26] and protected mice from colitis-associated colorectal cancer through its anti-inflammatory effects [27]. A recent report demonstrated an antitumor effect of DI on a thymic carcinoma cell line [28]; however, our data show for the first time as proof of principle a direct therapeutic effect of DI on primary leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The use of DI is currently proposed as a novel putative treatment strategy for several inflammatory-mediated diseases including cardiovascular diseases where a recent report showed that DI-loaded nanofibers reduce inflammation and help to repair myocardic infarction [16,[22][23][24][25]. In the context of cancer, DI showed anticancer activity in mouse models of hepatocellular carcinoma [26] and protected mice from colitis-associated colorectal cancer through its anti-inflammatory effects [27]. A recent report demonstrated an antitumor effect of DI on a thymic carcinoma cell line [28]; however, our data show for the first time as proof of principle a direct therapeutic effect of DI on primary leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In either liver or kidney tissue, the groups fed fortified feed led to a restored activity which was a result of Theobroma cacao protection. Urea is a waste product from the amino acid catabolism [61] while creatinine is the by-product of creatine catabolism [62] . The concentration of these products in the serum is regulated by the kidney; hence compromise in its functional status will lead to an increase in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Gautam et al. [ 162 ] reported DI is an anticancer drug for diethylnitrosamine-induced hepatocellular carcinoma in albino Wistar rats. Recently, we found 4-OI inhibited aerobic glycolysis by targeting GAPDH to promote cuproptosis in colorectal cancer in mice models [ 163 ].…”
Section: Introductionmentioning
confidence: 99%